Website as Digital Marketing Media of Ecotourism Medokan Ayu Mangrove Botanical Gardens in Rungkut District, Surabaya, East Java - Hariadi Yutanto Yutanto; Suhartono Suhartono Suhartono; Ellen Theresia Sihotang; Kartika Marta Budiana; Diah Ekaningtyas Ekaningtyas (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
Medokan Ayu Mangrove Botanical Garden is one of the ecotourism destinations, which is located on the east coast of the city of Surabaya, East Java. This ecotourism is managed by Tourism Awareness Group (Pokdarwis) Medokan Ayu in a conventional way. Before the COVID-19 pandemic, the number of tourist visits was quite a lot, which was more than 100 visitors per week. However, Pokdarwis Medokan Ayu faced problems during the pandemic of COVID-19. The number of visitors to Medokan Ayu Mangrove Botanical Garden decreased by almost 90% especially on weekends during July 2021. This problem could be solved by promoting of the Medokan Ayu Mangrove Botanical Gardens online through the Pokdarwis.id website. This community service aimed to design and implement digital promotion using the concept of Business Model Canvas (BMC). This community service activity was carried out using training methods containing four stages: coordination with partners, training, mentoring, and evaluation. Based on the results of observations, ten Pokdarwis administrators were able to operate the Pokdarwis website by filling content calendar and doing copywriting. This training had a positive response from the partner, especially the administrators, who suggested that the PkM team continue to provide mentoring with website management. The ability of the ten Pokdarwis administrators has also increased as evidenced by the increase and variety of news on the Pokdarwis website, and the implication that the number of website visitors increased to 3,515 by the end of February 2023. The number of visitors to the Medokan Ayu Mangrove Garden from mid-2022 to the end of January 2023 averaged 1,500 visitors per month.